KEBIJAKAN NON PENAL DALAM PENANGGULANGAN TINDAK PIDANA PENCABULAN TERHADAP ANAK DI KABUPATEN ROKAN HULU - Riyan Syahputra; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Children are creatures of God Almighty who have human rights like other humanbeings, so that no human or other party can rob them of these rights. Problems related tochildren often occur in Indonesia, for example regarding sexual abuse of children, includingwithin the jurisdiction of the Rokan Hulu Police. This obscene case is one of the prominentcases handled by the Rokan Hulu Police. The purpose of writing this thesis, namely; First, tofind out the factors that cause the occurrence of the Crime of Obscenity against Children inRokan Hulu Regency, Second, to know the non-penal policy in overcoming the crime ofobscenity against children in the Rokan Hulu Police, Third, to know the obstacles to non-penal policies in overcoming the crime of obscenity. against the Rokan Hulu Police, Fourth,to know about law enforcement efforts to overcome the crime of sexual abuse of children inRokan Hulu Regency.This This type of research can be classified in the type of sociological juridicalresearch, because in this study the author directly conducts research on the location or placeunder study in order to provide a complete and clear picture of the problem under study. Thisresearch was conducted at the Rokan Hulu Police and Penitentiary Class II B PasirPangaraian, while the Population and Sample are all parties related to the problems studiedin this study, the data sources used, primary data, secondary data, and tertiary data. Datacollection techniques in this study are observation, questionnaires, interviews, and literaturestudy.From the results of the research problem, there are four main things that can beconcluded, First, the factors that cause the occurrence of the Crime of Obscenity againstchildren in Rokan Hulu Regency are low education and economic factors, environment andplace of residence, alcoholic beverages, technology, and the role of the victim, Second, non-penal policies in overcoming criminal acts of sexual abuse against children at the Rokan HuluPolice are repressive measures and social actions such as providing sex education to childrenand shaping the child's personality in the family as well as conducting counseling to parents andschools, religious education, continuous raids, cooperation with relevant agencies andappointing environmental supervisors, Third, non-penal policy barriers in overcoming criminalacts of sexual abuse against children in the Rokan Hulu Police are factors of law enforcementofficers, supporting facilities or facilities, society and culture, as well as obstacles in handling ncases in the form of summoning witnesses, candid statements of victims, perpetrators beingcomplicated in providing information, and families of victims still holding grudges, Fourth, lawenforcement efforts to overcome criminal acts of sexual abuse against children in Rokan HuluRegency are to provide legal protection guarantees.Keywords: Non Penal, Obscenity, Children